The Health Benefits of Foods - Current Knowledge and Further Development 2020
DOI: 10.5772/intechopen.91167
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Natural Antioxidants and Future Perspectives

Abstract: Stress can exist by a variety of daily challenges related to obesity, other eating disorders, long-term health issues and immune system suppression. Free radicals derived from oxygen, called reactive oxygen species, reactive nitrogen species and similarly antioxidants are part of the body's natural functioning. Oxidative stress occurs when free radicals and antioxidants are out of balance. The prooxidantantioxidant balance is assessed by determination of both oxidant and antioxidant status, which can be measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 85 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…However, besides measuring the free radicals and other parameters in the antioxidant defense system, determination of the total oxidant and antioxidant status has been important to express the cumulative effect of oxidative stress in the organism. [ 34,63 ] An elevation of the formation of ROS and RNS in the lungs is effective in modulating redox signals. Therefore, they cause irreversible damage to highly important biomolecules such as enzymes, lipids, carbohydrates, and DNA, and initiate various pathogenic cellular processes as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides measuring the free radicals and other parameters in the antioxidant defense system, determination of the total oxidant and antioxidant status has been important to express the cumulative effect of oxidative stress in the organism. [ 34,63 ] An elevation of the formation of ROS and RNS in the lungs is effective in modulating redox signals. Therefore, they cause irreversible damage to highly important biomolecules such as enzymes, lipids, carbohydrates, and DNA, and initiate various pathogenic cellular processes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Besides measuring the free radicals and other parameters in the antioxidant defense system, the determination of the oxidant/antioxidant status (i.e., OSI) has been of great significance to express the cumulative effect of oxidative stress in organisms. [ 27,28,45 ] The present outcomes showed that ROS, TOS, and OSI levels considerably escalated, whereas TAS levels remarkably dropped in GalN given rats in both brain and cerebellum tissues. An increase in both ROS, TOS, and OSI levels and a decrease in TAS levels in these tissues of rats may indicate that oxidative stress occurs following GalN administration.…”
Section: Discussionmentioning
confidence: 52%
“…Spirulina platensis is the microalga the most frequently used as a supplement. It contains carotenoids, phycocyanin, xanthophylls and phycobilins, which have antioxidant activity (32,37).…”
Section: Introductionmentioning
confidence: 99%